Fast extraction of front ribbon resistance of silicon photovoltaic modules using electroluminescence imaging. (December 2019) - Rajput, Amit Singh; Rodríguez-Gallegos, Carlos D.; Ho, Jian Wei; Nalluri, Srinath; Raj, Samuel; Aberle, Armin G.; Singh, Jai Prakash
Highlights: Electroluminescence (EL) characterisation of photovoltaic modules is presented. The front-side ribbon resistance is extracted by analyzing two EL images of module. The method does not require prior information on solar cell properties. Abstract: A fast and non-destructive method based on electroluminescence (EL) imaging is presented to extract the front side resistive loss for individual cells within a crystalline silicon photovoltaic module. As the local luminescence intensity of a solar cell is an exponential function of local voltage, the voltage distribution along individual ribbons within the solar cell can be extracted. The front side resistance can then be computed using the distributive nature of current flow along the ribbon. As the soldering ribbons are much more conductive than the cell busbars, and due to the contact resistance between the cell busbars and soldering ribbons, the extracted front-side resistance describes mainly the front ribbon resistance. The method requires only two EL measurements on finished modules, which makes cell-to-module resistive loss analysis simple and fast. The proposed method is then compared with the measured and predicted voltage difference along the ribbon for individual solar cells. Simulation results are also presented and compared with our proposed method.